2020
DOI: 10.1108/ijppm-05-2019-0226
|View full text |Cite
|
Sign up to set email alerts
|

Corporate sustainability and enterprise performance

Abstract: PurposeThe purpose of this paper is to analyse the relationship between economic performance in terms of labour productivity of small- and medium-sized enterprises (SMEs) and their corporate sustainability in association with the driving forces of internationalization process and enterprise networks.Design/methodology/approachThe paper develops an innovative theoretical–conceptual approach and applied unique empirical survey to investigate the simultaneous causalities between labour productivity and corporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…In the context of SMEs, literature depicts the linkage of economic performance with the sustainability of the enterprises [87,97]. An interesting perspective for future studies could be to downstream these findings and contextualize the sustainability of ARIs with the economic performance of SMEs being moderated by various control variables and determine the causality.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SMEs, literature depicts the linkage of economic performance with the sustainability of the enterprises [87,97]. An interesting perspective for future studies could be to downstream these findings and contextualize the sustainability of ARIs with the economic performance of SMEs being moderated by various control variables and determine the causality.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of authors advocated that ESGP and CFP interact positively (e.g. Bojnec and Tom si c, 2021;Ghouri et al, 2020;Zhang et al, 2018;Fisher and Sawczyn, 2013;Orlitzky et al, 2003;Waddock and Graves, 1997), while some papers found a negative relationship between ESGP and CFP (e.g. Amran et al, 2016;Bansal, 2005;Hillman and Keim, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A growing number of studies in very different geographical settings have examined how alliances and networks of companies influence the application of sustainable practices by companies (Bojnec and Tom si c, 2021). The development of other partner relationships with sustainability objectives has also been explored, although their results have been limited and specific (Barbosa et al, 2022).…”
Section: Effects Of Distribution Channel Integrationmentioning
confidence: 99%